Diseño de una propuesta para la implementación de un sistema de costos para la microempresa “tu Café” en la ciudad de Bogotá en el año 2020 - Dionisio Useche, Juan Manuel; Torres Pulido, Indrí Alejandra (Universidad Antonio Nariño, 2021)
The present work of degree is oriented to the "DESIGN OF A PROPOSAL FOR THE IMPLEMENTATION OF A SYSTEM OF COSTS FOR THE MICRO-ENTERPRISE" YOUR COFFEE "IN THE CITY OF BOGOTÁ IN THE YEAR 2020" because the economic activity that the micro-enterprise is dedicated is the coffee production.. TU CAFÉ is a family micro-business belonging to Mr. Antonio Páez Galindo and is located in the center of Bogotá D.C. Currently, the microenterprise does not have a cost system; and the final price of the production is obtained from the calculations in an estimated way according to the experience in works carried out in previous years. In this system proposal it allows you to take into account all the expenses incurred in the coffee production process, determined the unit cost with greater precision, helping the entrepreneur to make better business decisions according to the sale price. As part of the research process, the production processes for the production of the microenterprise product will be examined, and a proposal will be made for a cost system that is more adapted. (Cabrera, 2012).